Designing a Website-Based Tracking Of Sales Information System to Improve Business Performance at Estoh Jember Company - Naila Rahmatul Widad; Wali Ja’far Shudiq; Anis Yusrotun Nadhiroh (Publikasi Indonesia, 2024)
Nowadays, technological developments are starting to accelerate and have changed so many aspects of human life, including in the field of business. Various technological advancements such as the internet, big data and artificial intelligence have changed the way businesses work. One small example of the use of technology in the business sector is to provide convenience for human resources in managing and processing data and also provide convenience in disseminating information so that it becomes faster and of course more guaranteed accuracy. With so many positive contributions produced, it is certain that the quality service provided will increase and be able to minimize the occurrence of violations and fraud in terms of employee discipline. So far, there are still many large companies that choose not to keep up with the times so that it has an impact on the company's service to its clients, such as manual supervision and monitoring of sales using selfies which has great potential in triggering fraudulent acts such as falsification of information by sales. Not only that, the sales performance recapitulation also becomes scattered and often causes problems in terms of making reports. Therefore, there is a need for a tracking of sales information system that can make it easier for companies to monitor and measure sales achievements in the field. This research was conducted to design a website-based information system by utilizing the sophistication of QRcode and Geolocation which is very easy to use and of course flexible. The method of designing this system uses the prototyping stage to produce a website-based tracking of sales information system that can improve the company's business performance.